The Effect of Work Motivation, Competence, and Organizational Culture on Employee Performance - Lina Mariana (Golden Ratio of Data in Summary, 2022)
The aims of this study were to: 1) determine and analyze the effect of motivation on employee performance at the Majene Regency Personnel and Human Resources Empowerment Agency, 2) Determine and analyze the influence of competence on employee performance at the Majene Regency Personnel and Human Resources Empowerment Agency, and 3 ) Knowing and analyzing the influence of organizational culture on employee performance at the Agency for Personnel and Human Resources Empowerment Majene Regency. The data used are primary data and secondary data. The population in this study consisted of all Civil Servants (PNS) at the Majene Regency Personnel and Human Resources Empowerment Agency, amounting to 42 people. By looking at the number of populations that are not too large, this study uses the census method, namely the entire population as respondents. Data was collected through observation, questionnaires, and documentation. The data analysis method used descriptive statistical analysis, and multiple linear regression using the SPSS program. The results showed that the variables of motivation, competence, and organizational culture had a positive and significant effect on employee performance at the Majene Regency Personnel and HR Empowerment Agency. Of the three independent variables used in determining the level of employee performance, it turns out that the motivational variable has a dominant influence in improving employee performance at the Majene Regency Personnel and Human Resources Empowerment Agency.